Evaluation of the dynamicity of mitotic exit network and spindle position checkpoint components on spindle pole bodies by Fluorescence Recovery After Photobleaching (FRAP) - Caydasi, Ayse Koca; Pereira, Gislene (The Mitotic Exit Network, 2017)
Fluorescence recovery after photobleaching (FRAP) is a powerful technique to study in vivo binding and diffusion dynamics of fluorescently labeled proteins. In this chapter, we describe how to determine spindle pole body (SPB) binding dynamics of mitotic exit network (MEN) and spindle position checkpoint (SPOC) proteins using FRAP microscopy. Procedures presented here include the growth of the yeast cultures, sample preparation, image acquisition and analysis.
Gesehen am 21.12.2020